2005
DOI: 10.1179/sic.2005.50.supplement-1.63
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and strain measurement techniques for the inspection of damage in works of art

Abstract: The engineering techniques used for inspecting structural damage are not widely known in the conservation sector. Techniques are available based on deformation or strain measurement that have the ability to provide quantitative data. This paper reviews currently available techniques, covering point-strain measurements using resistance strain gauges and fibre-optic sensors, as well as full-field optical measurement approaches such as holography, electronic speckle pattern interferometry, photoelastic stress ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…Further, the so called percussion method has been described, in that the sound emitted by the painting upon a slightly tapping on the surface is interpreted [22,168]. The investigation of cultural heritage objects by NDT has been reviewed a few years ago [20].…”
Section: Non Destructive Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the so called percussion method has been described, in that the sound emitted by the painting upon a slightly tapping on the surface is interpreted [22,168]. The investigation of cultural heritage objects by NDT has been reviewed a few years ago [20].…”
Section: Non Destructive Testingmentioning
confidence: 99%
“…These advanced analytical techniques also find application in the investigation of cultural heritage objects. A number of papers, commonly focusing on a single or small number of similar techniques, have been describing these applications [6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Overviews dealing with established techniques for the analysis of easel paintings have also been published in book chapters [1,26].…”
Section: Introductionmentioning
confidence: 99%
“…ESPI has proved to be a very attractive tool, especially for in-situ investigation on frescoes, wooden panels and museum objects (Gülker, 1990), (Boone, 1995), (Paoletti, 1996), (Lucia, 1997), (Schirripa Spagnolo, 2003), (Ambrosini, 2004), (Dulie-Barton, 2005), as well as on different artworks such as mosaics (Schirripa Spagnolo, 1998), canvas (Young, 1999, and terracotta warriors (Gülker, 2001). ESPI can also be used to monitor the artwork conditions over time as well as the effect of sunshine on frescoes (Hinsch, 2007).…”
Section: Figmentioning
confidence: 99%
“…A pilot study had concluded that effective strain monitoring of textiles required a combination of a full-field measurement technique with reference sensors, with two techniques identified as particularly promising (Dulieu-Barton et al, 2005). These were firstly, a full-field, strain measurement technique based on 3D photogrammetry, known as digital image correlation (DIC); and secondly, point measurement of strain obtained via optical fibre sensors.…”
Section: Introductionmentioning
confidence: 99%